Overt and occult hepatitis B virus infection among community children in Northwest China. Issue 9 (19th April 2017) - Su, H.; Shao, Z.; Pu, Z.; Wang, Y.; Zhang, L.; Zhang, W.; Wang, B.; Wang, A.; Ji, Z.; Yan, Y.; Zhang, Y.
Summary: Although a universal newborn hepatitis B (HB) immunization programme has been implemented in China, hepatitis B virus (HBV) breakthrough infection, including HB surface antigen (HBsAg)‐positive infection and occult HBV infection (OBI), still occurs during infancy or childhood. Obtaining the actual prevalence of HBV infection in general children is important for preventing and controlling the spread of HB. Accordingly, we investigated the prevalence of overt infection and OBI in community children and compared the serological and virological characteristics of OBI and HBsAg carrier children to clarify the mechanisms related to OBI. In total, 6 706 community children <12 years of age were included from a population‐based HBV seroepidemiological investigation in Northwest China. The HBsAg carrier rate in community children was 1.60% (107/6706), and the anti‐HBs positive rate was 57.35% (3846/6706). Additionally, 1192 HBsAg‐negative children were examined for OBI using nested PCR. The prevalence of OBI in local children was 1.26% (15/1192), and the predominant OBI genotypes were C and D. The 15 OBI children and 29 HBsAg‐positive children from the same population did not have a statistical significant difference in age, gender, alanine aminotransferase (ALT), proportion of anti‐HBs or anti‐HBc, viral genotypes or mutations. Children with chronic overt infection had higher viral loads than OBI children ( P =.004). These results suggested that HBV overt and occult infection of children was more serious in underdeveloped north‐west regions. HBV neonatal immunization and catch‐up programmes should be strengthened and supplemented. None of specific viral mutations or genotypes related to OBI were found. OBI may be a specific stage of HBV infection.